The Relationship between Acceptance and Caregiving Burden in Parents of Children with Intellectual Disabilities - Fitria, Yeni; Widiyantari, Ni Made Galuh; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Universitas Airlangga, 2025)
Introduction: Parents of children with intellectual disabilities often deal with complex emotional and psychological challenges. This can affect parents' acceptance of their child's condition. Parental acceptance plays an important role in determining the ability to manage caregiving burden, which will have an impact on childcare. This study aims to analyze the relationship between acceptance and caregiving burden in parents of children with intellectual disabilities. Method: This study used a cross-sectional design with total sampling technique involving 74 respondents. Inclusion criteria were biological parents who live together and care for children with intellectual disabilities at SLB-C TPA Jember and SLB Negeri Jember. Data was collected using the Parental Acceptation-Rejection Questionnaire (PARQ) and Zarit Burden Interview (ZBI) and analyzed using Kendall's Tau-C correlation test. Results: The results showed that most respondents 68 (91.9%) had a high acceptance, while 42 (56.8%) experienced a mild burden. The p- value = 0.005 and the coefficient correlation r=-0,298, shows that there is negative relationship with a weak correlation between parental acceptance and caregiving burden in parents of children with intellectual disabilities. Conclusions: This study found that there is relationship between parental acceptance and the caregiving burden. The higher the parental acceptance, the lower the caregiving burden. Parents who can accept their children with intellectual disabilities tend to be more ready to deal challenges and are able to perform their parenting role with an adaptive attitude. Parental acceptance can reduce the perception of caregiving burden. The findings highlight that parents should increase their acceptance to children with intellectual disabilities to deal with parenting challenges more easily.